Розробка стратегії управління людськими ресурсами в готельно-ресторанному бізнесі - Миць, Юрій; Кушнірик, Руслана (Видавництво Львівської політехніки, 2025)
This thesis examines strategies for human resource management in the hotel and restaurant industry. It emphasizes the strategic importance of skilled personnel as a competitive advantage and the challenges posed by high turnover in the hospitality sector. The study analyzes key HR strategies such as targeted recruitment and retention programs, comprehensive employee training and motivation systems, and the cultivation of a positive organizational culture. Modern HR tools – including electronic HRM systems, people analytics, mobile HR applications, e-learning platforms and gamification – are discussed as means to enhance efficiency and engagement. The review concludes that integrating traditional HR practices with digital innovations and a people-centric corporate culture significantly improves staff loyalty, productivity, and service quality in hospitality enterprises.
Keywords: управління персоналом; готельно-ресторанний бізнес; HR-стратегія; корпоративна культура; мотивація персоналу; цифрові HR-технології